Apport de l'analyse des réseaux sociaux à l'étude des communautés d'apprentissage en ligne - Cédric Sarré (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
In spite of the amount of published research on the use of computer-mediated communication (CMC) in second language acquisition (SLA) in the past twenty years, few of these studies deal with voice-based CMC (audioconferencing and videoconferencing) and with how it compares with text-based CMC. This article aims at bridging this gap by examining and comparing learner-to-learner interactions in L2 English that were generated during the completion of collaborative tasks using three different CMC modes: text chat, desktop videoconferencing and discussion board. The collaborative tasks to be completed were part of a blended learning system called English for Biologists whose main objective was to help learners develop their interactional competence in L2. The sociometric analysis of the interactions generated made it possible to highlight the influence of the CMC mode on the interactional load and configuration of the interactions, and to demonstrate how successful telecollaboration was in all three cases. Conclusions can also be drawn from it regarding the impact of CMC modes on the integration of learners in their learning community.